Anxiety level before and during the match of uhamka pencak silat athletes - Rizal, Bayu Thomi; Kasriman, Kasriman (Universitas Suryakancana, 2022)
This study aims to determine the description and differences in the level of anxiety of athletes before and during the match. The sample in this study were 33 pencak silat athletes from Tapak Suci Uhamka who had participated in National, International events, or who had carried out tryouts. Sampling using total sampling technique. Data collection was carried out with an anxiety test instrument, the implementation of filling out a questionnaire using Google Form. The research method used in this research is descriptive qualitative survey method. Data analysis was carried out in several stages, namely (1) data reduction, (2) data presentation, and (3) data verification and then analyzed using percentage descriptive analysis technique. For the results of the data obtained by 22.22% indicators before the game, and 28.28% on indicators during the game. This study concluded that the anxiety of the pencak silat athlete Uhamka was influenced by two indicators, namely before and during the match. Anxiety that arises during the match affects the pencak silat athlete of Tapak Suci Uhamka in the match more than the anxiety that arises before the match.Key words: Anxiety, Pencak Silat, Tapak Suci.